A coupled FEM-GDQM approach for vibration analysis of stiffened and laminated composite plates - Arikoglu, Aytac; Serveren, Mert; Demir, Ozgur (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This paper studies free vibration of stiffened and laminated composite plates by a combined finite element method (FEM) and generalized differential quadrature method (GDQM) approach. Stiffener and plate equations are obtained by the Hamilton's principle and they are combined by the use of Dirac-delta function. A novel approach for the solution of such PDEs by the GDQM is proposed. The stiffener model is formulated in its most general form i.e., it carries out axial, bending, lateral bending and torsion deformations. Torsional rigidity of composite stiffeners is calculated by a novel numerical torsion experiment conducted via an in-house FEM code. The results of the proposed framework are validated against the ones found in the literature and commercial FEM software and a very good agreement is observed.
Keywords: Stiffened composite plates; Finite element method (FEM); Generalized differential quadrature method (GDQM); Torsional rigidity; Vibration analysis; FINITE-ELEMENT-ANALYSIS; TORSIONAL RESPONSE; DYNAMIC-ANALYSIS; SANDWICH PLATES; RIGIDITY; SHELLS; Engineering; Oceanography